Residual effects of natural bush, Cajanus cajan, and Tephrosia candida on the productivity of an acid soil in southeastern Nigeria - Gichuru, M.P. (1991)
An experiment was established in 1986 to examine the contribution of Tephrosia candida and Cajanus cajan shrubs to improving the productivity of an acid soil. The main treatments were N levels (0 and 60 kg ha-1) with subplots of maize/natural bush, maize/Tephrosia candida, maize/Cajanus cajan, maize + cassava/natural bush, maize + cassava/Tephrosia candida, and maize + cassava/Cajanus cajan. In 1988, all plots were cleared and maize uniformly planted to study the residual effects of the treatments. No residual effects of N application were observed. Tephrosia candiada and Cajanus cajan increased surface soil organic carbon and total N levels over the natural bush. However, only Tephrosia candida plots produced improved maize grain and stover yield. Highly significant correlations were found between maize grain yield and earleaf N (r=0.73**), grain N (r=0.51**), and stover N (r=0.54**) contents. These results suggest that Tephrosia candida increased N availability in the soil. Therefore, the shrub has potential for improving the productivity of acid soils under traditional systems, where N is limiting due to the absence of N2-fixing legumes in the natural bush fallow.